(untitled) (Nonconventional Technologies Review, 2025)
The paper deals with the presentation of the methods for depassivating the iron hydroxide layer in electrochemical-ultrasonic hybrid machining. Ultrasonic depassivation, specific to the electrochemical-ultrasonic hybrid machining, was studied using the specialized software Comsol Multiphysics, focusing on the removal of the passivated iron oxide layer through the action of ultrasonic cavitation induced in the machining working gap. Before defining the parameters in Comsol Multiphysics to build the geometry of the elements needed for modeling and simulation, the shear fatigue resistance of iron oxide and the implosion time of cavitation bubbles were calculated using Rayleigh’s equation. An experimental equipment was constructed to test and validate the research carried out with the aid of specialized software tools.